Monitoring patients and asymptomatic carriers with hereditary transthyretin amyloidosis: regional protocol of Emilia-Romagna ATTR working group - Guaraldi, Pietro; Allegri, Isabella; Ariatti, Alessandra; Baldini, Tommaso; Barbieri, Andrea; Barocelli, Federico; Bartolotti, Michela; Biagini, Elena; Bianchi, Francesca; Borghi, Annamaria; Borghi, Claudia; Boriani, Giuseppe; et al. (Frontiers in Neurology, 2025)
Transthyretin amyloidosis (ATTR) is a rare disease caused by the extracellular accumulation of misfolded transthyretin (TTR) amyloid fibrils. ATTR can be either hereditary (ATTRv) or acquired (wtATTR). ATTRv is caused by a mutation in the transthyretin gene (TTR) with an autosomal dominant pattern of inheritance. In ATTRv amyloidosis, some patients primarily exhibit symptoms of polyneuropathy others mainly or exclusively present with symptoms of cardiomyopathy. However, many patients present with a multisystemic involvement that includes sensory, motor, autonomic, and cardiac symptoms. Early diagnosis and detection of disease progression are emerging as a crucial need for ATTR amyloidosis in order to significantly impact survival, patients’ functions and quality of life. Currently, parameters to be monitored in ATTR patients in the real life might refer to some publicly available recommendations regarding the monitoring and assessment of disease progression in the real-world setting of patients with ATTRv. Nonetheless, a standardized disease monitoring protocol has not been established in Italy, posing a significant unmet need for a prompt and equal access to care. Therefore, in the Emilia-Romagna Region the “ATTR Working Group” has sought to tailor the recommendations to the Regional “real clinical setting” in order to optimize and standardize a monitoring protocol aimed at identifying disease progression. Patients’ and carriers’ access to uniform monitoring routes across the entire Region ensures optimal disease management and economic sustainability.